6 MV photon beam induced UV/VIS absorption of hema polymer gel - Siti Atiqah Ishak,; Iskandar Shahrim,; Siti K.A.R.,; Azhar A. Alrahman, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aim of this study was to evaluate properties of normoxic polymer gel 2-Hydroxyethyl methacrylate monomer (HEMAG) as a point dosimeter by using optical properties evaluation techniques. HEMAG were prepared from seven different radiation dose within five different depths of HEMAG dosimeters. These HEMAG dosimeters were irradiated by linear accelerator with 6 MV photon beams. The absorption spectra were measured by using a UV-visible spectrophotometer in the wavelength range from 300 to 800 nm. Then, the data was analysed to determine the optical energy band gap (Eg) and Urbach’s energy (ΔE). The result showed that Eg and ΔE were dependent on radiation dose and percentage of depth dose (PDD). In additional, Eg with indirect transition of HEMAG decreased as radiation dose increased and increased with traversing of depth. ΔE of HEMAG increased as the dose increased and decreased with traversing depth of monomer. There was a shift in the Eg values towards lower energy as the dose increased and led to a shift of the ΔE value towards the higher energy with increasing dose. This observation supported the increase of structured disorder of the polymer with increasing radiation dose, which resulted in the lower energy transitions that was feasible and reduced the values of Eg. In conclusion, HEMAG has a potential to be used as a dosimeter at low radiation dose in the clinical radiotherapy.